Answer:
D. x = 4 and x = 3
Step-by-step explanation:
The first step is to add 12 to both sides, like so:
[tex]x^2 - 7x = -12\\[/tex]
+12 + 12
___________
[tex]x^2[/tex] - 7x + 12 = 0
Split the middle term (7x) into two numbers that can be multiplied to get 12, and be added to get 7:
[tex]x^2[/tex] - 4x - 3x + 12 = 0
Group:
([tex]x^2[/tex] - 4x) (-3x + 12) = 0
Take out GCF (Greatest Common Factor):
x(x - 4) -3(x - 4) = 0
(x - 3) (x - 4) = 0
Set them both equal to 0:
x - 3 = 0 x - 4 = 0
+ 3 + 3 + 4 + 4
________ _______
x = 3 x = 4